Identification of salt tolerant barley genotypes for coastal region of Bangladesh (Bangladesh Journal of Botany, 2008)
Identification of salt tolerant barley (Hordeum vulgare L.) genotypes and effects of different levels of salinity on their growth, grain development and yield were studied. One hundred and eighty nine barley germplasms were subjected in five levels of NaCl concentration which were equivalent to Electrical Conductivity (EC) of 0, 10, 15, 20 and 25 ds/m. Among the genotypes 39 proved to be saline tolerant at 15 ds/m of salinity. Out of 39 genotypes, 33 were evaluated at Sonagazi and Patuakhali salt area of Bangladesh. All the genotypes were evaluated in the non-saline area at BARI, Gazipur to observe their performance in normal soil. Highest grain yield was recorded from the genotypes BSH-32 and BSH-142 over the three locations. Significantly higher yield was recorded from the experimental site of Gazipur followed by Patuakhali and Sonagazi. Tiller per plant had positive correlation with grain per spike, maturity and grain yield. Grain per spike and maturity was positively correlated with grain yield. From the multivariate analysis it appears that 1st, 2nd and 3rd principal components together account for 79 per cent of the total experimental variation. The two selected genotypes are expected to be released for commercial cultivation in the saline area of Bangladesh.       Key words: Barley, Genotypes, Selection, Salt tolerant, Bangladesh DOI = 10.3329/bjb.v36i2.1504 Bangladesh J. Bot. 36(2): 151-155, 2007 (December)